A Systematic Literature Review on the Effect of Traditional Games in Mathematics Teaching and Learning (Scopus Database) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Much research has shown the positive effect of traditional games on supporting students in learning mathematics. This systematic literature review (SLR) aims to explore research findings on implementing traditional games in mathematics teaching and learning. Through a tight screening process using PRISMA 2020 Framework, we identified 16 articles from the Scopus Database that align with the purpose of this SLR. The result of this SLR showed that research about the implementation of traditional games in mathematics classrooms had been primarily conducted in Asia regions, especially Indonesia; primary school students are frequently the subject of research; geometry is the most frequent mathematics topic taught using traditional games; cognitive ability is more frequent as a research focus, in term of effect of the implementation of traditional games; qualitative approach mostly applied for the study; and start from 2018 the research about the implementation of traditional game in mathematics instruction is still being carried out.